Examining live-in foreign domestic helpers as a coping resource for family caregivers of people with dementia in Singapore - Basnyat, Iccha; Chang, Leanne (Taylor & Francis, 2016)
In Singapore, the responsibility of caring for persons with dementia falls on family members who cope with long - term caregiver burden depending on available support resources. Hiring foreign domestic workers to alleviate caregiver burden becomes a prevalent coping strategy that caregivers adopt. This strategy allows caregivers to provide home care as part of fulfilling family obligations while managing caregiver burden. This study aimed to investigate primary caregivers’ relationship with hired support and its impact on coping with caregiver burden. Twenty in-depth interviews were conducted with primary caregivers who hired live-in domestic helpers to take care of their family members with dementia. The findings revealed that caregivers perceived the normative obligations to provide home care to family members with dementia. They sought support from domestic helpers to cope with physical and mental burnout, disruption of normal routines, and avoidance of financial strain. A mutual-support relationship was built between caregivers and domestic helpers through trust and interdependence. The presence of domestic helpers as a coping resource reveals the positive outcomes of problem, emotional, and diversion focused coping. This study illustrates that coping strategies are employed in different ways depending on the needs of caregivers, access to infrastructure, cultural expectations, and available resources.